An Estimation of Signal Emitter Parameters from the Amplitude Measurements by an ESM Receiver - PHAM, V. T.; HUBACEK, P. (Advances in Electrical and Computer Engineering)
In passive radar data processing, some emitter parameters can be extracted from the amplitude data measured by an Electronic Support Measures (ESM) receiver over a specific time. This article focuses on retrieving characteristic parameters such as irradiation time (IT), maximum amplitude (AMP), and emitter antenna pattern shape from the measured amplitude of the received signal using the method of nonlinear data fitting. A new algorithm was proposed to enhance the accuracy of these parameter estimations based on the emitter antenna pattern characteristics. Besides, the new information obtained on the antenna pattern shape and its beamwidth (BW) can also be exploited for emitter recognition and classification. Several numerical simulations were implemented to evaluate the accuracy of the proposed method in computing the IT, the maximum AMP, and the emitter antenna pattern BW compared to the other methods.